Formation of Protoplasts from Resting Spores - Fitz-James, Philip C. (1971)
Coat-stripped spores suspended in hypertonic solutions and supplied with two essential cations can be converted into viable protoplasts by lysozyme digestion of both cortex and germ cell wall. Calcium ions are necessary to prevent membrane rupture, and magnesium ions are necessary for changes indicative of hydration of the core, particularily the nuclear mass. Since remnant spore coat covered such protoplasts of Bacillus subtilis and the germ cell wall of B. cereus spores is not lysozyme digestible, coatless spores of B. megaterium KM were more useful for these studies. Lysozyme digestion in cation-free environment produced a peculiar semi-refractile spore core free of a cortex but prone to rapid hydration and lytic changes on the addition of cations. Strontium could replace Ca(2+) but Mn(2+) could not replace Mg(2+) in these digestions. When added to the spores, dipicolinic acid and other chelates appeared to compete with the membrane for the calcium needed for stabilization during lysozyme conversion to protoplasts. It is argued that calcium could function to stabilize the inner membrane anionic groups over the anhydrous dipicolinic acid-containing core of resting spores.